Climate services impact assessment generates evidence of more than 500,000 farmers reached by a comprehensive Climate Risk Management (CRM) strategy of eleven Latin American countries - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Co-developed, tested, and scaled out by CCAFS scientists, climate services approaches are helping assess, produce, translate and transfer climate information to enable agricultural decision making to 420+ institutions in eleven countries in Latin America (LAM), reaching 501,000 farmers in a comprehensive national Climate Risk Management (CRM) from the local level to the national and regional levels, and allowing the generation of a powerful governance structure for rural development and community-level resilience.